Bond strength and deflection of a hard chair side reline material to two denture base resins - Mahro vojdani; Sina Safari; Mitra Farzin (Isfahan University of Medical Sciences, 2010)
Introduction: Bond Strengths among denture base resins and various types of reline materials are not always satisfactorily high. Therefore efforts have been made to use materials similar to resin base dentures and bonding agents to increase infirmity. This study compares bond strength and deflection of a hard chair side reline material with two denture base resins.Materials and Methods: In this experimental study, 54 resin specimens with the size of 65×10×2.5 mm were prepared. These specimens included intact heat cure (M), cold cure (F), acrylic resin specimens bonded with the same resins (M-M, F-F) and specimens bonded to a hard chair side reline material (M-G, F-G). All specimens were stored in sodium hypochlorite 8 hours a day for 3 months and were then thermocycled (2000 cycles, 5 to 55°C). The transverse bond strengths (FMax) and deflections (DFMax) were evaluated with three point loading test. The results were analyzed with two-way ANOVA followed by Games Howell & Gabriel's and Kolmogrov-smirnor test (α = 0.05).Results: F Max for different types of resins and reline materials showed significant differences (p value < 0.05). Although DFMax differences between reline materials and their interactions with different types of resins were significantly different (p value < 0.05), no significant difference among the types of resins could be found (p value = 0.263). Comparing the reline materials with denture base resins, cold cure resin was shown to have statistically different FMax and DFMax (p value < 0.05). Heat cure resins showed statistical differences on FMax between intact resins when relined with the same resins and relined with hard reline (p value < 0.05).Conclusion: Bond strength of the cold cure denture base resin group (F) to the same resin was higher than hard reline, but bond strength of hard reline material with heat cure denture base was similar to the bond strength of the same reline, and in this group , maximum deflection in bonded resin with the same resins were showed. Key words: Flexure, Bond, Denture base, Dental resin, Reline material.